Standalone DC microgrids as complementarity dynamical systems: Modeling and applications. (February 2015) - Dizqah, Arash M.; Maheri, Alireza; Busawon, Krishna; Fritzson, Peter
Abstract: It is well known that, due to bimodal operation as well as existent discontinuous differential states of batteries, standalone microgrids belong to the class of hybrid dynamical systems of non-Filippov type. In this work, however, standalone microgrids are presented as complementarity systems (CSs) of the Filippov type which is then used to develop a multivariable nonlinear model predictive control (NMPC)-based load tracking strategy as well as Modelica models for long-term simulation purposes. The developed load tracker strategy is a multi-source maximum power point tracker (MPPT) that also regulates the DC bus voltage at its nominal value with the maximum of ±2.0% error despite substantial demand and supply variations.